2019
DOI: 10.1093/annonc/mdy500
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel with or without trametinib or pazopanib in advanced wild-type BRAF melanoma (PACMEL): a multicentre, open-label, randomised, controlled phase II trial

Abstract: Background Advanced melanoma treatments often rely on immunotherapy or targeting mutations, with few treatment options for wild-type BRAF ( BRAF -wt) melanoma. However, the mitogen-activated protein kinase pathway is activated in most melanoma, including BRAF -wt. We assessed whether inhibiting this pathway by adding kinase inhibitors trametinib or pazopanib to paclitaxel chemotherapy improved outcomes in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The addition of chemotherapy to Pazopanib treatment has been tested in malignant melanoma with manageable toxicity. The foremost grade 3 toxicity was increase in alanine aminotransferase [21]. The combination of radiation therapy with pazopanib had been tested in the adjuvant treatment of breast cancer patient who developed less dermatological toxicity than matched control groups treated with radiation therapy alone [22].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of chemotherapy to Pazopanib treatment has been tested in malignant melanoma with manageable toxicity. The foremost grade 3 toxicity was increase in alanine aminotransferase [21]. The combination of radiation therapy with pazopanib had been tested in the adjuvant treatment of breast cancer patient who developed less dermatological toxicity than matched control groups treated with radiation therapy alone [22].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in PFS between paclitaxel plus pazopanib and single paclitaxel therapy. 27 Our meta-analysis study found that patients with targeted therapy were predisposed to a better clinical outcome in a patient with the positive BRAF gene mutation. Moreover, combination therapy has a better prognosis than monotherapy, probably due to the resistance mechanism.…”
Section: Discussionmentioning
confidence: 79%
“…In a phase II study of sunitinib in patients with advanced melanoma, 4/31 (13%) patients exhibited a partial response and 8 (26%) had stable disease (52). Pazopanib, a VEGF and platelet-derived growth factor inhibitor, has been used in combination with paclitaxel in a phase II study of patients with metastatic melanoma; the 6-month progression-free survival rate was 68%, and the 1-year overall survival rate was 48% (53). The objective response rate was 37%, comprising one complete and 20 partial responses (54).…”
Section: Discussionmentioning
confidence: 99%